Fiscal Consolidation During Times of High Unemployment : The Role of Productivity Gains and Wage Restraint - Lama, Ruy.; Medina Guzman, Juan Pablo (Washington, D.C. : International Monetary Fund, 2015)
This paper studies the Swedish fiscal consolidation episode of the 1990s through the lens of a small open economy model with distortionary taxation and unemployment. We argue that the simultaneous reduction in the fiscal deficit and unemployment rate in this episode stems from two factors: (i) high growth rates of total factor productivity (TFP), experienced after the implementation of structural reforms; and (ii) a sustained wage restraint that occurred during the 1990s. The model simulations show that economic growth, accounted for mostly by TFP gains, improved the fiscal balance by 8 percentage points of GDP through an expansion of the tax base and fiscal revenues. Moreover, the combination of stable wages and higher TFP boosted net exports and led to a reduction in the unemployment rate. A counterfactual simulation assuming stagnant TFP shows that fiscal consolidation measures alone would have generated a double-digit unemployment rate without eliminating the fiscal deficit.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet